Hard Red and Soft Red Winter Wheat Variety Testing – 2024 - Gretchen F. Sassenrath; Garth Blackburn; Jane Lingenfelser; Xiaomao Lin (Kansas Agricultural Experiment Station Research Reports, 2025)
This is a summary of the winter wheat production conditions in Kansas, with particular emphasis on the variety trial results from southeast Kansas in 2024. The fall of 2023 was dry, slightly impacting wheat establishment, but overall yields were above average of previous variety trials. Overall yields in the variety tests were much higher than the state averages at Parsons for both hard and soft wheat varieties. Above average rainfall in the spring did not result in significant disease pressure.
Keywords: hard red winter wheat; soft red winter wheat; variety testing; Kansas wheat production